The Importance of the Infrastructures in the Italy South: the Case of the Naples Port - Rossella Murgolo (European Regional Science Association (ERSA), 2006)
Over the last few years, the European Union has much stressed both the increasing efficiency of passengers and goods' mobility and ports representing crucial links in the whole transport network. Recent documents by the European Commission have largely dealt with European policies on transports trying to find the means to guarantee a free and fair competition both among different ports and for different competitor transport modes to match management and charging in European ports. This paper aims to find the ports and sea infrastructures in the South of Italie, with respect to Naples port, with a view to realize some recovery works, seen by a juridical and cheap poin of view. The paper, leaving from the competitive analysis of big reconversions of the ports at national and international level, analyses the passengers traffic in order to determine a model of development of the Naples port.
Keywords: 330